A prospective clinical pilot study on the level of matrix metalloproteinase-9 in dental pulpal blood as a marker for the state of inflammation in the pulp tissue - Mente, Johannes; Petrovic, Jelena; Gehrig, Holger; Rampf, Sarah; Michel, Annemarie; Schürz, Alexander; Pfefferle, Thorsten; Saure, Daniel; Erber, Ralf (Journal of endodontics, 2016)
INTRODUCTION: Differentiation between reversible pulpitis (savable pulp) and irreversible inflammation of the pulp tissue (nonsavable pulp) based only on clinical and radiographic diagnoses has proven to be difficult. Pulp exposure allows for the collection of pulpal blood to quantitatively determine the level of inflammation markers or proteolytic enzymes, even with small samples. Pulpitis is associated with the invasion of neutrophil granulocytes and their release of matrix metalloproteinase-9 (MMP-9). - METHODS: Forty-four patients (aged 18-74 years, mean = 35 years), each with 1 tooth with carious pulp exposure presenting with different stages of pulpitis, were included in this prospective, 2-center clinical study; 26 patients presented with irreversible pulpitis (groups 3 and 4), 10 with reversible pulpitis (group 2), and 8 with completely asymptomatic teeth with deep carious lesions (group 1). Six of the 26 patients with teeth diagnosed with irreversible pulpitis had not taken any nonsteroidal anti-inflammatory drugs and were evaluated as a separate group (group 4). Partial pulpotomy and blood sample collection from the pulp chamber were performed. The total levels of MMP-9 and tissue inhibitor of metalloproteinase-1 were assessed by fluorometric and colorimetric enzyme-linked immunosorbent assays, respectively. The Mann-Whitney U test and Spearman rank correlations were used to compare the MMP-9 levels with different stages of pulpal inflammation; significance was set at .05. - RESULTS: The MMP-9 levels in the asymptomatic teeth (group 1) were significantly different from those in the teeth with reversible pulpitis (group 2, P = .006) or irreversible pulpitis (group 4, P < .001). A statistically significant difference was also observed between the MMP-9 levels in group 1 and group 3 (P < .001) in which the patients had taken nonsteroidal anti-inflammatory drugs. - CONCLUSIONS: These findings indicate that the MMP-9 levels in pulpal blood samples could be a useful ancillary diagnostic tool for distinguishing different stages of pulp tissue inflammation.